If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2z + 1)(5 + -1z) = 0 Reorder the terms: (1 + 2z)(5 + -1z) = 0 Multiply (1 + 2z) * (5 + -1z) (1(5 + -1z) + 2z * (5 + -1z)) = 0 ((5 * 1 + -1z * 1) + 2z * (5 + -1z)) = 0 ((5 + -1z) + 2z * (5 + -1z)) = 0 (5 + -1z + (5 * 2z + -1z * 2z)) = 0 (5 + -1z + (10z + -2z2)) = 0 Combine like terms: -1z + 10z = 9z (5 + 9z + -2z2) = 0 Solving 5 + 9z + -2z2 = 0 Solving for variable 'z'. Factor a trinomial. (5 + -1z)(1 + 2z) = 0Subproblem 1
Set the factor '(5 + -1z)' equal to zero and attempt to solve: Simplifying 5 + -1z = 0 Solving 5 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1z = 0 + -5 -1z = 0 + -5 Combine like terms: 0 + -5 = -5 -1z = -5 Divide each side by '-1'. z = 5 Simplifying z = 5Subproblem 2
Set the factor '(1 + 2z)' equal to zero and attempt to solve: Simplifying 1 + 2z = 0 Solving 1 + 2z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2z = 0 + -1 2z = 0 + -1 Combine like terms: 0 + -1 = -1 2z = -1 Divide each side by '2'. z = -0.5 Simplifying z = -0.5Solution
z = {5, -0.5}
| 10x-92=3x-8 | | 2x+5x=20.34 | | -1/5w-3/2=2w-7/5 | | sin(37)=x/14 | | 2x+9-10=2(x-5)+12 | | (-5x+3)+(-7x-1)= | | -2y-(0)=2y-8 | | 1-3Y=3 | | 6+25x=15x+14 | | A+5=-4a+5 | | -2x+4=-6+26x | | 55-10x=19+8x | | 5m+7n-2(6m-8n)= | | 49/(-7)=-7k/(-7) | | -2(0)+x=2(0)-8 | | 90=-4x | | x=75(x)+7 | | (6-5i)+(7-2i)= | | 42-3x=12+12x | | 441+b*b=841 | | 3b/100 | | 27-4x=12-7x | | y=5/8=-1/4 | | 11x=-35+4 | | 2(x-6)+2x-10= | | .23x=.94 | | 12y=38x-100 | | 8x-(5x-7)= | | k/12=3 | | 5m-6=8 | | 3y/100 | | 38x+12y=100 |